HNC/HCN ratio in acetonitrile, formamide, and BrCN discharge - Ferus, Martin; Kubelík, Petr; Kawaguchi, Kentarou; Dryahina, Kseniya; Španěl, Patrik; Civiš, Svatopluk (The journal of physical chemistry. A, 2011)
Time-resolved Fourier transform (FT) spectrometry was used to study the dynamics of radical reactions forming the HCN and HNC isomers in pulsed glow discharges through vapors of BrCN, acetonitrile (CH(3)CN), and formamide (HCONH(2)). Stable gaseous products of discharge chemistry were analyzed by selected ion flow tube mass spectrometry (SIFT-MS). Ratios of concentrations of the HNC/HCN isomers obtained using known transition dipole moments of rovibrational cold bands v(1) were found to be in the range 2.2-3%. A kinetic model was used to assess the roles the radical chemistry and ion chemistry play in the formation of these two isomers. Exclusion of the radical reactions from the model resulted in a value of the HNC/HCN ratio 2 orders of magnitude lower than the experimental results, thus confirming their dominant role. The major process responsible for the formation of the HNC isomer is the reaction of the HCN isomer with the H atoms. The rate constant determined using the kinetic model from the present data for this reaction is 1.13 (±0.2) × 10(-13) cm(3) s(-1).